Simplified equivalent modelling of electromagnetic emissions from printed circuit boards - Tong, Xin (2010)
Characterization of electromagnetic emissions from printed circuit boards (PCBs) is an important issue in electromagnetic compatibility (EMC) design and analysis of modern electronic systems. This thesis is focused on the development of a novel modelling and characterization methodology for predicting the electromagnetic emissions from PCBs in both free space and closed environment. The basic idea of this work is to model the actual PCB radiating source with a dipole-based equivalence found from near-field scanning.